Creating the Ideal Community as A Root of Fethullah Gulenâ€™s View on Gender Equality - Khamami, Akhmad Rizqon (IAIN Ponorogo, 2019)
Abstract: This article discusses the roots of Gulen's view on gender equality and its roles within the movement, which constitutes an example of an Islamic movement that can adapt in the contemporary era and becomes progressive Islam. Conversely, Gulenâ€™s view on gender belongs to the conservative movement. By employing functionalism, this article tries to seek and delve into the theme. It further argues that the movements' mission to create â€œthe ideal communityâ€ is the driving ideology on gender relations. Examining some important scholarly findings on the movement and works by its founder Fethullah Gulen, the womenâ€™s position is unequally subordinated to that of men, as their initial functions to obey their husbands and to maintain familyâ€™s honor. Importantly, their role is limited to educate their children to deliver